Impact of HCV eradication by directly acting antivirals on glycemic indices in chronic hepatitis C patients -a nationwide Taiwan HCV registry - Tyng-Yuan Jang; Chung-Feng Huang; Te-Sheng Chang; Chun-chi Yang; Ching-Chu Lo; Chao-Hung Hung; Chien-Wei Huang; Lee-Won Chong; Pin-Nan Cheng; Ming-Lun Yeh; Cheng-Yuan Peng; Chien-Yu Cheng; et al. (Journal of the Formosan Medical Association, 2025)
Background/Aims: Hepatitis C virus (HCV) eradication using antiviral agents augments the metabolic profile. Changes in glycated hemoglobin (HbA1c) levels in chronic hepatitis C patients who receive glecaprevir/pibrentasvir (GLE/PIB) remain elusive. Methods: Data from 2417 patients treated with GLE/PIB from the Taiwan HCV Registry were analyzed, and pretreatment HbA1c levels were compared with 3-months after the-end-of treatment levels. A sustained virological response (SVR) was defined as undetectable HCV RNA at 12 weeks after the end of treatment. A significant change in HbA1c level was defined as the 75th percentile of the change in the HbA1c level before and after treatment (decrement >0.2%). Results: Serum HbA1c levels decreased significantly (6.0 vs 5.9%, P < 0.001). Post-treatment HbA1c levels decreased in all subgroups, except in non-SVR patients (5.7 vs 5.7%, P = 0.79). Compared to patients without significant HbA1c improvement (decrement >0.2%), those with HbA1c improvement were older (60.2 vs 58.6 years, P < 0.001), had higher serum creatinine levels (1.9 vs 1.6 mg/dL, P < 0.001), triglycerides (129.8 vs 106.2 mg/dL, P < 0.001), fasting glucose (135.8 vs 104.0 mg/dL, P < 0.001), and pretreatment HbA1c (7.1 vs 5.7%, P < 0.001) and had a higher proportion of male sex (57.9% vs 50.9%, P = 0.003), diabetes (84.3 vs 16.8%, P < 0.001), more advanced stages of chronic kidney disease (CKD) (15.7 vs 11.1 %, P < 0.001), anti-diabetic medication use (47.3 vs 16.4%, P < 0.001) and fatty liver (49.6 vs 38.3 %, P < 0.001). Multivariate analysis revealed that the factors associated with significant HbA1c improvement were age (odds ratio [OR]/95% confidence intervals [CI]: 1.01/1.00–1.02, P = 0.01), HbA1c level (OR/CI: 2.83/2.48–3.24, P < 0.001) and advanced CKD stages (OR/CI: 1.16/1.05–1.28, P = 0.004). If the HbA1c variable was not considered, the factors associated with significant HbA1c improvement included alanine aminotransferase level (OR/CI, 1.002/1.000–1.004, P = 0.01), fasting glucose level (OR/CI: 1.010/1.006–1.013, P < 0.001), and diabetes (OR/CI: 3.35/2.52–4.45, P < 0.001). Conclusion: The HbA1c levels improved shortly after HCV eradication using GLE/PIB. The improvement in glycemic control can be generalized to all subpopulations, particularly in patients with a higher baseline HbA1c level or diabetes.